Identification of HIVEP2 as a dopaminergic transcription factor related to substance use disorders in rats and humans - Zhao, Juan; Chen, Chunnuan; Bell, Richard L; Qing, Hong; Lin, Zhicheng (Translational psychiatry, 2019)
Playing an important role in the etiology of substance use disorder (SUD), dopamine (DA) neurons are subject to various regulations but transcriptional regulations are largely understudied. For the first time, we report here that the Human Immunodeficiency Virus Type I Enhancer Binding Protein 2 (HIVEP2) is a dopaminergic transcriptional regulator. HIVEP2 is expressed in both the cytoplasm and nuclei of DA neurons. Therein, HIVEP2 can target the intronic sequence GTGGCTTTCT of SLC6A3 and thereby activate the gene. In naive rats from the bi-directional selectively bred substance-preferring P vs -nonpreferring NP rat model of substance abuse vulnerability, increased gene activity in males was associated with the vulnerability, whereas decreased gene activity in the females was associated with the same vulnerability. In clinical subjects, extensive and significant HIVEP2-SLC6A3 interactions were observed for SUD. Collectively, HIVEP2-mediated transcriptional mechanisms are implicated in dopaminergic pathophysiology of SUD.
Keywords: DNA vazebné proteiny; Animals; Female; dopaminergní neurony; transkripční faktory; ženské pohlaví; lidé; Cell Nucleus; Transcription Factors; buněčné jádro; Dopamine Plasma Membrane Transport Proteins; regulace genové exprese; Dopaminergic Neurons; Sex Factors; Male; sexuální faktory; DNA-Binding Proteins; proteiny přenášející dopamin přes plazmatickou membránu; krysa rodu Rattus; Substance-Related Disorders; Gene Expression Regulation; zvířata; mužské pohlaví; poruchy spojené s užíváním psychoaktivních látek; Mice, Inbred C57BL; Rats; myši inbrední C57BL; Humans